2004
DOI: 10.4315/0362-028x-67.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Listeria monocytogenes on the Surface of Individually Packaged Hot Dogs with a Packaging Film Coating Containing Nisin

Abstract: The objective of this study was to determine the effectiveness of packaging films coated with a methylcellulose/hydroxypropyl methylcellulose-based solution containing 10,000, 7,500, 2,500, or 156.3 IU/ml nisin for controlling Listeria monocytogenes on the surfaces of vacuum-packaged hot dogs. Barrier film coated with a methylcellulose/hydroxypropyl methylcellulose-based solution containing nisin or no nisin (control) was heat sealed to form individual pouches. Hot dogs were placed in control and nisin-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…Hence, chitosan can be used as a natural antimicrobial coating on fresh strawberries to control the growth of microorganisms, thus extending shelf-life of the products Films and coatings based on cellulose or derivatives such as methyl cellulose (MC), carboxy methyl cellulose (CMC) or hydroxy propyl methyl cellulose (HPMC) containing antimicrobial compounds have been used to control microbial growth and extend the shelflife of several foods. In such sense, Franklin et al [40] determined the effectiveness of packaging films coated with a MC/HPMC-based solution containing 100, 75, 25 or 1.563 mg/ml nisin for controlling L. monocytogenes on the surfaces of vacuum-packaged hot dogs. They found that packaging films coated with a cellulose-based solution containing 100 and 75 mg/ml nisin significantly decreased (P ≤ 0.05) L. monocytogenes populations on the surface of hot dogs by greater than 2 logs CFU/g throughout the 60 days of storage.…”
Section: Carriers Of Antimicrobial Compoundsmentioning
confidence: 99%
“…Hence, chitosan can be used as a natural antimicrobial coating on fresh strawberries to control the growth of microorganisms, thus extending shelf-life of the products Films and coatings based on cellulose or derivatives such as methyl cellulose (MC), carboxy methyl cellulose (CMC) or hydroxy propyl methyl cellulose (HPMC) containing antimicrobial compounds have been used to control microbial growth and extend the shelflife of several foods. In such sense, Franklin et al [40] determined the effectiveness of packaging films coated with a MC/HPMC-based solution containing 100, 75, 25 or 1.563 mg/ml nisin for controlling L. monocytogenes on the surfaces of vacuum-packaged hot dogs. They found that packaging films coated with a cellulose-based solution containing 100 and 75 mg/ml nisin significantly decreased (P ≤ 0.05) L. monocytogenes populations on the surface of hot dogs by greater than 2 logs CFU/g throughout the 60 days of storage.…”
Section: Carriers Of Antimicrobial Compoundsmentioning
confidence: 99%
“…In hot dogs that were vacuum-packaged in fi lms coated with nisin, L. monocytogenes counts decreased during refrigeration storage (Franklin et al 2004 ). Hot dogs were placed in control and nisin-containing pouches and inoculated with a fi ve-strain L. monocytogenes cocktail (approximately 5 log CFU per package), vacuum sealed, and stored for intervals of 2 h and 7, 15, 21, 28, and 60 days at 4 °C.…”
Section: Semi-processed and Cooked Meatsmentioning
confidence: 99%
“…10 Different types of antimicrobial agents including organic acids and their salts, nitrites, antibiotics, alcohols, enzymes, bacteriocins, especially nisin have been incorporated into packaging fi lms. 11 Franklin et al 12 found that packaging fi lms coated with a cellulose-based solution containing 10 000 and 7500 IU/ml nisin signifi cantly decreased L. monocytogenes populations on the surface of hot dogs by greater than 2 log CFU/package throughout the 60 day study.…”
Section: Introductionmentioning
confidence: 99%